Refleksi Sejarah Orde Baru pada Novel Namaku Alam - Apriyani, Tristanti; Daulay, Resneri (Lingua Susastra, 2023)
Literary works offer an in-depth and subjective perspective on a historical event. Historical events that may not be fully documented can be revived through literary works. This research aims to find a reflection of the history of the New Order using the Newhistoricism approach formulated by Greenblatt (1980) in Leila S. Chudori's latest work entitled Namaku Alam. This research is a type of qualitative descriptive research using content analysis techniques. Based on the nature of the new historicism approach, data collection was carried out using a parallel reading method between literary and non-literary texts. Data analysis techniques were carried out using archaeological methods and in-depth description methods. The results of the research prove that the historical events of the New Order that were discovered included the arrest of people who were related to the PKI along with the negative stigma received by political prisoners and their descendants; personal hygiene and environmental cleanliness policies; supervision of people's reading; and petition 50.